Etude du pouvoir antifongique des huiles essentielles de quatre plantes aromatiques (Lavandula sp., Origanum sp., Salvia officinalis et Thymus sp.) vis-à-vis du champignon Fusarium sp. - MEDJAHERI, Habiba; MEHADJRI, Feriel (My University, 2020)
The present work focuses on the evaluation of the antifungal activity of essential oils (EOs) of four aromatic plants against the fungus Fusarium sp. The objective of this study is to valorize these natural resources in order to find alternatives based on the use of natural products to fight against pathogens. The antifungal power of the EOs of Lavandula sp., Origanum sp., Salvia officinalis and Thymus sp. was evaluated by the direct contact method on the PDA medium. Through this modest work, all the results obtained show that the EOs of Origanum sp. and Thymus sp. succeeded in perfectly inhibiting the mycelial growth of Fusarium sp. in comparison with the effect of the EOs of Lavandula sp. and S. officinalis. Indeed, total inhibition of colony growth was observed for the three highest doses of Origanum sp. and Thymus sp. EOs (0.1%, 0.05% and 0.025%). While for the highest dose (0.1%) inhibition rates below 96% and 52% were recorded for EOs of S. officinalis and Lavandula sp., respectively.
Keywords: Antifungal activity; essential oils (EOs); Lavandula sp.; Origanum sp.; Salvia officinalis; Thymus sp. and Fusarium sp